Artificial Intelligence (AI) Modeling Technique to Improve Creative Thinking on Number Concepts for Early Childhood with Disabilities - Indah Rahayu Panglipur; Hersiyati Palayukan; Lucky Dewanti (South Sulawesi Education Development (SSED), 2024)
Downsindromes need media to help them focus on learning and understand the material about numbers. Subjects who are classified as active behavior may have creative thinking abilities that need to be explored. The purpose of this study was to determine how the application of video media with artificial intelligence (AI) articulation with modeling techniques and the results of improving creative thinking skills in down syndrome disabilities. Qualitative research with an approach to data analysis using descriptive was conducted to obtain data. The method of interview, observation with the help of video recording was used in data collection. The results of this study state that learning carried out using video media with artificial intelligence articulation with modeling techniques can be applied well, indicated by SDS can be active and focused in participating in learning activities. The increase in creative thinking skills from the beginning has not appeared at all creative thinking skills to the results obtained that SDS has the ability to think creatively with 2 indicators appearing, namely flexibility and originality.